Low back pain in women before and after menopause - Kozinoga, Mateusz; Majchrzycki, Marian; Piotrowska, Sylwia (Menopause Review/Przegląd Menopauzalny, 2015)
Low back pain is a massive problem in modern population, both in social and economic terms. It affects large numbers of women, especially those aged 45-60. Going through a perimenopausal period is associated with many symptoms, including low back pain. This paper is a review of published research on the association between the perimenopausal age and low back pain. PubMed databases were investigated. After the search was narrowed to “menopausal status, back pain”, 35 studies were found. Seven studies, which suited our area of research best, were thoroughly analyzed. All studies show increased pain when women enter this period of their life. There is no agreement among researchers regarding which stage of menopause is the most burdensome. Examples of possible treatments and physiotherapeutic methods targeting low back pain are also presented. Physiotherapeutic procedures used to treat low back pain include exercises in safe positions, balance exercises, manual therapy, massage and physical measures.